Gimnazjaliści wobec narkotyków = Middle school students and drugs - Lipińska-Lokś, Jolanta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Social conditions in which we live raise great interest among scientists and in other social spheres. An average individual is bombarded with information. This information evokes emotions-sometimes so immense that it is difficult to deal with them, understand the cause of some facts, and accept their consequences. Many people fail in dealing with the modern world. It seems that those whose conditions of life are very difficult tend to be more exposed to threats. Personality traits are also important. The age of a person is meaningful as well.
Keywords: narkotyki; gimnazjaliści; badania